Rancang Bangun Sistem Informasi Pengolahan Nilai Rapor Berbasis Web Pada SMK Negeri 1 Kotaraja - Dwi Utami Putra, Desak Made; Ariansidi, Mohamad (INFOTEKS (Information Technology, Computer and Sciences), 2019)
Assessment is the technique of evaluating students as the result of a learning achievement. Final assessment at SMK Negeri 1 Kotaraja is a report or student’s learning outcomes sheets. The process of calculating values at SMK Negeri 1 Kotaraja has been used still the conventional method process by using a list of score that given by teachers that have the possibility lost, tucked, and scattered. Even it will easily human error and quite complicated because there are many scores that have to calculated, such as daily test scores and assignment scores that have to be calculated each average score, steps used are very complicated so it takes about 7 days to process its, That is why the distribution of report cards to the students becomes delayed. Based on the problem above, it is aimed to create an information system of scoring processing report on web based that could helped teacher of SMK Negeri 1 Kotaraja in more effective and efficient processed. The results of blackbox testing that has been done stated that information system of scoring processing report that helped could teacher performance and help students esier in accessing online report.